Micro - and macromechanical properties of sintered steel with different porosity. (August 2022) - Tomić, Zoran; Gubeljak, Nenad; Jarak, Tomislav; Polančec, Tomislav; Tonković, Zdenko
Abstract: To assess the behaviour of porous materials, it is important to consider the influence of material microstructure. In this study, a multiscale experimental analysis is conducted to investigate the influence of micromechanical parameters, such as the material properties of metallic phases and porosity, on the macromechanical properties of a porous sintered steel. At the microlevel, indentation is conducted to identify microphases and metallographic analysis has been used on mesoscale to measure porosity. Tension uniaxial tests have been applied to characterize macro properties. The results of the tests suggest that the macromechanical properties of porous sintered metallic materials might be mostly influenced by the porosity, while at the microlevel no significant variation in the mechanical properties of microphases has been detected in samples with different density, i.e., porosity. In addition, porosity is related to the sintering density experimentally and an empirical expression that relates density and porosity is proposed. Graphical Abstract: Image, graphical abstract .